2018
DOI: 10.3171/2017.10.focus17566
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of lateral lumbar interbody fusion without decompression for the treatment of symptomatic degenerative spondylolisthesis at L4–5

Abstract: OBJECTIVERecently, authors have called into question the utility and complication index of the lateral lumbar interbody fusion procedure at the L4–5 level. Furthermore, the need for direct decompression has also been debated. Here, the authors report the clinical and radiographic outcomes of transpsoas lumbar interbody fusion, relying only on indirect decompression to treat patients with neurogenic claudication secondary to Grade 1 and 2 spondylolisthesis at the L4–5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…The superiority of LLIF for spondylolisthesis reduction has been reported in several studies [5,10,15], and LLIF was also reported to be effective in the reduction of even grade II spondylolisthesis [30]. However, a previous study comparing it to TLIF reported that LLIF had no advantage in terms of spondylolisthesis reduction [15].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The superiority of LLIF for spondylolisthesis reduction has been reported in several studies [5,10,15], and LLIF was also reported to be effective in the reduction of even grade II spondylolisthesis [30]. However, a previous study comparing it to TLIF reported that LLIF had no advantage in terms of spondylolisthesis reduction [15].…”
Section: Discussionmentioning
confidence: 96%
“…TLIF provides a good visualization of the neural elements through direct decompression of the posterior element [8,12]. LLIF approaches the intervertebral disc space through retroperitoneal transpsoas (DLIF/XLIF) or extrapsoas (OLIF) and indirectly decompresses the spinal canal and intervertebral foramen by inserting a cage with large footprint [5,10,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent symptoms, again primarily thigh sensorimotor loss, were seen in 4-5% of patients with the difference in definition between transient and persistent somewhat arbitrary at a cut-off of 6 months [12]. A small series of 18 patients in which LLIF was used to treat spondylolisthesis patients found a third (33%) of the patients developed sensory deficit of the thigh but also that all had resolved within 6 months postoperatively [13]. Similarly, another small series from a different institution evaluating this same procedure and pathology found 3 in 16 (19%) patients developed transient sensory loss that resolved within 1 year.…”
Section: Thigh Symptomsmentioning
confidence: 99%
“…A variety of techniques of lumbar interbody fusion have been used to help alleviate pain from lumbar spine-related disease [1][2][3]. For the past few decades, the minimally invasive spinal surgical technique has emerged as an alternative approach to the more invasive open lumbar interbody fusion procedure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%